Prevalence and associated factors of lower extremity musculoskeletal disorders among manufacturing workers: a cross-sectional study in China. Issue 2 (2nd February 2022) - Jin, Xu; Dong, Yidan; Wang, Fujiang; Jiang, Ping; Zhang, Zhongbin; He, Lihua; Forsman, Mikael; Yang, Liyun
Abstract : Objective: To survey the prevalence of lower extremity musculoskeletal disorders (MSDs) among Chinese manufacturing workers, and to identify the associated factors. Design: Observational study with cross-sectional design. Setting: A self-administered questionnaire survey was conducted in four manufacturing factories in China. Participants: 7908 manufacturing workers were included in this study after excluding non-conforming personnel. Outcome measures: Individual and work-related information, and MSDs in the whole leg and knee region were measured by the anonymous self-administered questionnaire. Individual and work-related factors associated with MSDs and their effects were identified through multivariate logistic regression. Results: Of all respondents, 3241 (41.0%) reported having had lower extremity MSDs in the recent 12 months, and for the knees, ankles/feet and hips/thighs were 29.5%, 23.9% and 16.7%, respectively. After confounder-adjusted single-factor analysis, 22 variables (of 24) were significantly related to the disorders. Factors like always kneeling/squatting for long periods, always standing for long periods and often lifting in an uncomfortable position were shown to have higher risks, with ORs of 2.77 (95% CI: 2.33 to 3.30), 2.30 (1.96 to 2.69) and 2.25 (2.04 to 2.47). Comparable results were found on knee disorders. The final model included 15 variables of demography, biomechanics and work organisation. The following factors showed increased risks of lower extremity MSDs: being female, being older, longer working years, higher body mass index (BMI), keeping the same posture for a long time, awkward position, shift work and monotonous work. Whereas having enough breaks reduced the risk. Conclusion: The prevalence of lower extremity MSDs among Chinese manufacturing workers is high. The most commonly affected body regions were the knees and ankles/feet. Multiple factors were found associated with lower extremity MSDs including age, BMI, work experience, work organisations, physical ergonomics exposures, etc.